The Case of Cyprus: The Impact of a Participatory Designmodel of Inquiry-based Learning Environments on Student Motivation - Georgiou, Yiannis; Kyza, Eleni A.; Paraskeva-Hadjichambi, Demetra; Kofina-Michael, Zoe; Hadjistyllis, Andreas; Miliotis, George (My University, 2014)
uring the last decades, science education stakeholders have made several efforts to explore how to improve science teaching, since in most cases, science education fails to motivate or to meaningfully engage young learners (Eurydice Network, 2011). In many cases, traditional science education has been criticized for employing expository didactic approaches as well as focusing explicitly on teaching rote facts, without helping students to relate science to their own lives (e.g. Fensham, 2004; Holbrook, 2003). In an effort to address this problematic situation, a growing movement sees inquiry-based learning to be of paramount importance, since it has the potential to support students’ active engagement with scientific practices such as the investigation of important societal issues (Eurydice network, 2011; NRC, 2012). If one purpose of science education is to produce students, who can be actively engaged with science, then inquiry-based learning environments can provide an ideal venue for the accomplishment of this goal.
Keywords: Science education stakeholders; Science teaching